Scaffolding Problem Solving in Teaching and Learning The DPACE Model - A Design Thinking Approach - Malliga K Govindasamy; Ngu Moi Kwe (Research in Social Sciences and Technology- OpenED Network, 2020)
Problem solving is a basic skill needed to function effectively in the working environment. Teachers are no exception to this professional demand. It is of utmost importance for teacher education programs to prepare pre-service teachers with this fundamental competency. The DPACE model is a preliminary effort by two teacher educators to enhance the problem-solving skills among pre-service teachers. The model was developed using the design thinking approach with reference to Vygotsky’s constructivism and grounded by questions as scaffolds to facilitate internalization of knowledge that teachers need to assist them in addressing and expanding their problem-solving boundaries. The main structure of the model consists of five domains developed with reference to computational thinking concepts. Each domain consists of open-ended questions formulated according to Bloom’s ordering of cognitive skills, taking pre-service teachers progressively toward better understanding of the problem and creating an efficient solution. This model was applied among 62 pre-service teachers enrolled in the TSLB3152 course at the Teacher Education Institute International Languages Campus, Kuala Lumpur, Malaysia. In total, 86.67% of the respondents reported that the DPACE model helped them in their problem-solving task and almost 78% of them scored an A grade in their coursework tasks facilitated using the DPACE model. Efforts are needed to further refine the questions and field test the model in other courses or situations with the hope that this ongoing teacher education effort will create a paradigm shift in the quest toward mastery of 21st century skills among pre-service teachers.